The correct name for Adenocalymma comosum (Bignoniaceae) - Turner, Ian (Phytotaxa, 2015)
A large, golden-flowered, bignoniaceous liana native to Brazil and sometimes grown as a tropical ornamental is generally known as Adenocalymma comosum (Cham.) DC. in Candolle (1845: 201). The name is based on Bignonia comosa Chamisso (1833: 691). This is homonymous with Bignonia comosa Roxburgh (1832: 103). William Roxburgh first published this binomial in the Hortus Bengalensis (Roxburgh 1814) for a species introduced to the Calcutta Botanic Garden, India, from the Moluccas. Here, the name is a nomen nudum as there was no description included or reference made to a previously published description. Roxburgh’s brief description of the species was published posthumously in the third volume of Flora Indica (Roxburgh 1832). This appeared in late 1832 (Stafleu & Cowan 1983: 957). Roxburgh’s plant was actually Clerodendrum lanuginosum Blume (1826: 810) (Lamiaceae) (van Steenis 1967).